Purification and self-assembly of natural coiled-coil proteins from marine snail pugilina cochlidium egg case membranes - Loke, Jun Jie (2013)
Pugilina cochlidium is a marine snail that can lay a string of egg capsules made of an elastic biomaterial that encapsulates and protects the embryos from the harsh marine environments. Previous studies on Busycotypus canaliculatus, a different species of marine snail has found that the egg capsule is resilient and has shock absorbing properties. It exhibited elastic recovery which is non-entropy driven.